2016
DOI: 10.1007/s11528-016-0077-9
|View full text |Cite
|
Sign up to set email alerts
|

Peer Teaching in a Flipped Teacher Education Classroom

Abstract: More and more school administrators are expecting new teachers to flip their classrooms prior to completing their teacher certification. The purpose of this study was to explore the experiences of preservice teachers who facilitated learning in a flipped classroom, to identify the benefits and challenges of flipped instruction on preservice teachers, and to explore the impact of the course design on students' understanding of the course content. Results indicate that flipped lessons taught by students were int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 17 publications
2
49
1
2
Order By: Relevance
“…Studies in related literature show that videos are often used as a means of teaching outside the classroom, while interactive tasks in which the students are actively participating are used as in-class activities (Basal, 2015;Graziano, 2017;Herreid & Schiller, 2013;Hsu, 2017;Lage, Platt, & Treglia, 2000;Roehling, Root Luna, Richie, & Shaughnessy, 2017;Song & Kapur, 2017;Zengin, 2017). Active participation and student-centered learning can be ensured through the use of videos that maintain students' attention and enable them to concentrate on the content (Herreid & Schiller, 2013).…”
Section: Who's Flipping?mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in related literature show that videos are often used as a means of teaching outside the classroom, while interactive tasks in which the students are actively participating are used as in-class activities (Basal, 2015;Graziano, 2017;Herreid & Schiller, 2013;Hsu, 2017;Lage, Platt, & Treglia, 2000;Roehling, Root Luna, Richie, & Shaughnessy, 2017;Song & Kapur, 2017;Zengin, 2017). Active participation and student-centered learning can be ensured through the use of videos that maintain students' attention and enable them to concentrate on the content (Herreid & Schiller, 2013).…”
Section: Who's Flipping?mentioning
confidence: 99%
“…In recent studies, the impacts of the FC Model on student performance, engagement, learning outcomes, and motivation have been investigated. Studies have shown that the FC approach enhances student's learning performance (Baepler, Walker, & Driessen, 2014;Davies et al, 2013;Janotha, 2016;Sun & Wu, 2016;Talley & Scherer, 2013;Wiginton, 2013;Zengin, 2017;Zhonggen & Wang, 2016), produces enhanced learning outcomes (Chen Hsieh, Wu, & Marek, 2017;Gillispie, 2016;Kong, 2014;Smallhorn, 2017) and increases student motivation (Chyr, Shen, Chiang, Lin, & Tsai, 2017;Graziano, 2017;Smallhorn, 2017;Wiginton, 2013;Yılmaz, 2017).…”
Section: Impacts Of the Fc On Student Learningmentioning
confidence: 99%
“…Twelve people mentioned that when other students explain the information to them, it is easier to understand and allows them to deepen the aspects required to carry out the activities in the laboratory in a better way. In addition, because they are their peers, it increases the student-student relationship [37] and favors to solve learning difficulties [38]. In this way, there is greater confidence to ask questions about ideas or concepts that were not entirely clear, which is a bit intimidating when the professor is consulted.…”
Section: Resultsmentioning
confidence: 99%
“…This method will give students the opportunity to express their initial ideas and then confirm them with their peers. Some researchers have shown positive results in the use of peer teaching methods in universities in various applied sciences (Teixeira et al 2015;Graziano, 2017;Sayer, Marshman & Singh, 2016).…”
Section: Discussionmentioning
confidence: 99%